PENGEMBANGAN MODUL YANG DILENGKAPI PETA KONSEP BERGAMBAR PADA MATERI KLASIFIKASI MAKHLUK HIDUP UNTUK SMP - Suryaningsih, Rika; Widiana, Rina; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRACTIn theaching and learning process, the students are hoped to get benefit of learning biology and know in which case the concept can be implemented, furthermore, it is necessary for the teacherÂ  to create learning atmosphere that will help the student in understanding the concept. To make the student easier in understanding the material, the teacher as a facilitator should be able to create and adapt students need with any source of material. The learning sources that was not still understandable and interesting can bother learning process so that it is needed a development of learning sources that can be in the form of module. Based on the case above, it was done the research which had a purpose to create a module that was completed by drawing map concept in material âklasifikasi Makhluk Hidupâ for junior high school students, to know validity and practicality criterion. This research was a developmental research which was used three phase of 4-D model, it consisted of define, design, and develop. The subject of this research was 3 lecturers of biology, 2 teachers of SMP N 2 Pantai Cermin. Practicality testing by 2 Biology teachers and 29 students class VII SMP. Analysis of the data used descriptive and percentage technique. Based on the research result, it produced a product of module, the percentage score for the module which was categorized valid by the validator was 85,08%. Then, module which was categorized practice by teacher was 88,59% and by the students was 87,85%. from the easy used and learning efficiency therefore, it can be concluded that the module that was completed by drawing concept mapping had validity and practicality criterion.Â Â Â